2018
DOI: 10.1136/bmjopen-2018-023914
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and mental health outcomes and association with quality of life among adults living with HIV: a cross-sectional focus on a low-literacy population from coastal Kenya

Abstract: ObjectivesOur aim was to compare the neurocognitive performance and mental health outcome of adults living with HIV on antiretroviral therapy with that of community controls, all of low literacy. Furthermore, we also wanted to explore the relationship of these outcomes with quality of life among adults living with HIV.Study designThis was a descriptive cross-sectional study.SettingThe study was conducted in Kilifi County, a region located at the Kenyan coast.ParticipantsThe participants consisted of a consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
4
22
0
1
Order By: Relevance
“…A researcher-developed sociodemographic questionnaire was used to capture participant’s age, sex, marital status, educational level, employment status, and people with whom they were living with. Additionally, an asset index form previously used in this setting [10] was used to gather information on disposable assets owned by participants as an indicator of their socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A researcher-developed sociodemographic questionnaire was used to capture participant’s age, sex, marital status, educational level, employment status, and people with whom they were living with. Additionally, an asset index form previously used in this setting [10] was used to gather information on disposable assets owned by participants as an indicator of their socioeconomic status.…”
Section: Methodsmentioning
confidence: 99%
“…Depression has deleterious consequences on the wellbeing and overall health of PLWHA. It may lead to alteration of economic productivity [8], reduced cART adherence [9], and poor quality of life [10]. Studies from SSA reported that depression is associated with poorer overall health status [11], increases the risk for suicidality [12], leads to faster disease progression and increased mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…With ART, PLWH have the potential to live near normal life spans, notwithstanding preexisting comorbid conditions or complications that develop over time. Functional cognitive impairments in PLWH on ART are less frequent and less severe (Nyongesa et al, 2018;Sacktor et al, 2001); current estimates suggest that 15-20% of PLWH exhibit functional cognitive impairment that impacts activities of daily living (Heaton et al, 2010;Robertson et al, 2007;Woods et al, 2009). An additional 25-30% are reported to have a milder form of cognitive impairment that does not impact activities of daily living (Goodkin et al, 2001;Woods et al, 2009), although these individuals are more likely to progress to symptomatic cognitive impairment (Grant et al, 2014).…”
Section: Brain Bioenergetics In People Living With Hiv-1 Cognitionmentioning
confidence: 99%
“… 4 5 Secondary to both biological and psychosocial factors, people living with HIV are at an increased risk of experiencing poor mental health 6 7 which negatively impacts on their health-seeking behaviours, adherence to antiretroviral treatments 8 and quality of life. 9 The prevalence of common mental disorders is also significantly higher among people living with HIV, irrespective of them being on ART, and is further impounded by stigma. 10 There is also a known bidirectional relationship between HIV and mental health, worsened by associated health and social inequalities.…”
Section: Introductionmentioning
confidence: 99%